Multivocal Survival: Narrative Agency and Ecological Ethics in The Year of the Flood - Tasnim, Zakiyah (International Journal of Language and Literary Studies, 2025)
This article explores storytelling as a critical survival strategy in Margaret Atwood’s The Year of the Flood, the second novel in her MaddAddam trilogy. Departing from existing scholarship that emphasizes biotechnology, environmental collapse, and capitalist critique, this study foregrounds narrative as a psychological, ethical, and political tool of resistance for marginalized characters. Drawing on ecocritical and feminist frameworks—including Karen Stein’s theory of narrative empowerment, Ursula Heise’s concept of multiscalar narration, and Rob Nixon’s idea of slow violence—the article analyzes Atwood’s multivocal structure through the perspectives of Toby, Ren, and Adam One. These three narrators illustrate how storytelling functions as a means of trauma processing, identity formation, and communal resilience. The article argues that Atwood presents narrative as a cultural technology of survival—one that preserves memory, fosters ecological consciousness, and challenges dominant technoscientific paradigms. In a world fractured by the climate crisis, Atwood reclaims storytelling as both epistemology and existential necessity